Speaking Korean : beginners - Haiyoung, Lee; Inkyo, Hwang (New Jersey USA : Hollym International, 2006)
Introducción -- Locatión -- Purchasing -- Weekends -- Appointment -- Food
Incluye 1 cd
General
Keywords: Koreano; Chino; Coreano para principiantes